Assessing the Impact of American Indian Peer Recovery Support on Substance Use and Health. Issue 4 (2nd October 2017) - Kelley, Allyson; Bingham, Dyani; Brown, Erika; Pepion, Lita
ABSTRACT: Peer Recovery Support (PRS) is emerging as a key intervention for communities and individuals as they address high rates of substance abuse and limited recovery resources. American Indian populations were among the first people to use concepts of PRS through abstinence-based revitalization movements and ceremonies. The present study examined the impact of PRS on substance use, emotional and psychological problems, and social connections among urban and reservation American Indian peers involved in a 3-year PRS program. A total of 224 individuals, 110 male and 114 female completed baseline GPRA. Of these, 65 peers completed baseline and 6-month follow-up GPRAs. Involvement in PRS decreased substance use significantly among peers. Peer attendance at voluntary self-help groups and support from family and friends increased as a result of PRS.